Introduction to Chern-Simons Theory - Adeifeoba, Ademola (My University, 2020)
The 2 + 1 Yang-Mills theory allows for an interaction term called the Chern-Simons term. This topological term plays a useful role in understanding the ﬁeld theoretic description of the excitation of the quantum hall system such as Anyons. While solving the non-Abelian Chern-simons theory is rather complicated, its knotty world allows for a framework for solving it. In the framework, the idea was to relate physical observables with the Jones polynomials. In this note, I will summarize the basic idea leading up to this framework.
Keywords: Braid Group; Chern-Simons; Knot theory: Jones polynomial; TQFT; Wilson Loop